2011
DOI: 10.3109/02770903.2011.613508
|View full text |Cite
|
Sign up to set email alerts
|

Airway Responsiveness Measured by Forced Oscillation Technique in Severely Obese Patients, before and after Bariatric Surgery

Abstract: Airway responsiveness is not related to BMI or to SAS. AHR in severely obese patients might be related to distal airway obstruction or low relative airway size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…The residual abnormality in R 5−20 suggests distal airway dysfunction that may relate to residual bronchial hyperreactivity that has been observed in response to methacholine post weight loss despite normalization of resting lung volume. [42] Of note, the present study included data mostly of female subjects in accord with the population concurring to the Bellevue Hospital Bariatric Center therefore if gender differences exist in the effects of restoration of lung volume on airway responsiveness, they could not be identified in the present study. [15].…”
Section: Discussionmentioning
confidence: 97%
“…The residual abnormality in R 5−20 suggests distal airway dysfunction that may relate to residual bronchial hyperreactivity that has been observed in response to methacholine post weight loss despite normalization of resting lung volume. [42] Of note, the present study included data mostly of female subjects in accord with the population concurring to the Bellevue Hospital Bariatric Center therefore if gender differences exist in the effects of restoration of lung volume on airway responsiveness, they could not be identified in the present study. [15].…”
Section: Discussionmentioning
confidence: 97%
“…Higher respiratory resistance with smaller lung volumes has been reported in morbidly obese people, but in our study, this finding was not reproduced; on the contrary, we found even better lung volumes, which could be an attribute of a bigger thoracic cage. 21,22 Recent results have included deep inspiration avoidance added to the methacholine protocol of bronchoconstriction to assess for other physiological measurements, but without further results. 23 We face the possibility that methacholine might not be a suitable technique for assessing BHR in the obese population.…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms are unresponsive to bronchodilators, but improvements have been widely reported with weight loss (33,35). Surprisingly, spirometry often shows little or no change in lung function with weight loss (1,31,33,47), which makes it challenging to explore the mechanisms that link obesity and weight loss to changes in lung function and associated pathologies. Furthermore, lung function is typically assessed in the upright position, but the respiratory symptoms of obesity worsen in the supine position (10) and are thought to contribute to sleep disturbances (42).…”
Section: Introductionmentioning
confidence: 99%
“…These changes can be assessed by using oscillometry to calculate respiratory system resistance (Rrs) and reactance (Xrs). Indeed, several studies have used oscillometry to report significant improvements in lung mechanics at 12-24 mo after weight loss surgery (1,31,47); however, it is not clear whether these changes are either directly related to the mechanical effects of weight loss or to other factors such as metabolic effects that are associated with weight loss but with a different temporal course (34). By investigating the changes in lung mechanics early after weight loss surgery, the mechanisms linking obesity and weight loss to changes in lung function may be better assessed.…”
Section: Introductionmentioning
confidence: 99%